(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article examines the necessity, essence and factors, goals, objectives and problems of managing the financial stability of an enterprise at the current stage of liberalization and modernization of the economy of the Republic. The advantages and specific features of a creative approach to effective measures for managing the financial stability of an enterprise in the prospects of the country’s socio-economic development are scientifically substantiated.